Study of polymorphism of DRB1 gen and associated with some growth traits in Turkish Awassi sheep - ناصر ميساء احمد; الانباري نصر نوري (Journal of Kerbala for Agricultural Sciences, 2016)
This study was undertaken at the Ruminants Researches Station (20 km west of Baghdad) pertaining to the Directorate for Agricultural Researches / Ministry of Agriculture, Reproductive laboratory at the College of Agriculture/University of Baghdad as well as Laboratory Bridge Musayyib specialist to technology and bio-analysis and molecular genetics, and analysis of molecular genetics from 01/03/2015 to 15 / 01/2016 .The aim of this study was determind polymorphism of gene DRB1 and relationship of this polymorphism with some growth traits.The distribution percentage of polymorphism of gene DRB1 in ewe's sample were 22.50 and 42.50 and 35.00% for each of the alleles A, B and C respectively. The variation among these percentages were highly significant (P≤0.01) showing that effect phenotype of gene DRB1 in on lambs birth , weaning weight and increase the weight gain was significant (P≤0.01), the body dimensions of the lambs at weaning did not affected by phenotype of the DRB1 gene with the exception of their dams chest circumference (P≤0.05). It can be conclud through the study of polymorphism of the gene DRB1 revealed possibility of adopted them in sheep improvement strategy to increased the economic gain in the breeding schemes, by selecting and crossing the highly growth lambs genotypes or phenotypes, the best growth of the lambs.